ENVIRONMENTAL SUSTAINABILITY IN THE AFTERMATH OF A PANDEMIC: A STUDY BASED ON TRIPLE BOTTOM LINE APPROACH - Bhardwaj, Ananya; Roy, Manas; Sethi, Krati (The journal of contemporary issues in business and government, 2022)
Our world is rapidly changing, from hunter-gathering to farming to capitalism, economic globalization, and political difficulty. It is vital to consume our scarce resources in a sustainable manner since people have always been consumers rather than replenishes of the earth's natural resources. By definition, sustainability is known as the capability of current genesis to fulfill their requirements without jeopardizing the prerequisite of generations of the future ability to fulfill their own. Expressing in other words, it providethe ability of humans to live in harmony with the ecosystem on our planet. Environment sustainability as a conspicuous element of sustainability approaches towards steering definite resources to curb down the transforming resource as well as curtail down generated wastage by providingenvironmental and naturally generatedsources a protection sheet. These recent catastrophic circumstances have been the cause for the authors to rethink their understanding of their concept of sustainability. The COVID-19 pandemic has had a profound impact on human sustainabilitythrough “ triple bottom line (TBL)” approach consisting of pliers like “ economic, social, and environmental” . The research on COVID-19 and its long-term consequences is notably fragmented, owing to a growing interest among academics in acknowledging to the pandemic's immediate call for action implementing a concept known as the triple bottom line strategy is one way to achieve these future sustainable developmental goals.